COMMUNICATION PROTOCOLS, A BASIS FOR THE DIGITALIZATION OF INDUSTRIAL PROCESSES: Communication protocols, a basis for the digitalization of industrial processes - Cuero Granobles, Luis Felipe
The digital transformation of industrial processes is initially focused on obtaining process data, to later convert them into information that allows making timely decisions, to obtain improvements in the process value chain.  Machine-machine communication, M2M, is aimed at the exchange of information between machines in an industrial process, which has allowed the implementation of distributed control systems. The Internet of Things, IoT, a technology proposed by industry 4.0, is raising the possibility of communication not only at the machine level, but also communication with customers, suppliers, with all the actors in the company's value chain. This horizontal and vertical communication is being achieved through communication protocols such as MQTT, RFID, OPC UA, protocols based on Ethernet IP, which are the object of study in this project. This article presents the characterization of some of the communication protocols used in IoT, for which simulation applications are used to obtain and validate information from sensors and actuators of a manufacturing line; when carrying out the analysis of the evaluation of each one of the protocols used for this study, the high performance of the OPC UA protocol was determined, over the others studied. OPC UA is a quite viable alternative for communication, supported by its easy implementation, it is embedded in a considerable number of programmable automatons such as the S7 1500 PLCs from Siemens, the BOSCH PLCs, in addition to its communication speed, such as the packet size that it supports, allows adjusting to the needs of an IIoT environment.